SELECTION OF OXIDES FOR STABILIZATION OF ZIRCONIUM DIOXIDE WHILE OBTAINING THERMAL BARRIER COATINGS - V. V. Okovity (Наука и техника)
The paper analyzes selection of oxides and describes in details a majority of oxide systems which are applicable for stabilization of zirconium dioxide while obtaining thermal barrier coatings with maximum amount of tetragonal phase. Methodology of investigation is based on a review of analytical information on the current state of thermal barrier coatings on the basis of zirconium dioxide stabilized by oxides of rare-earth metals. The method used for application of  zirconium dioxide thermal barrier coatings is plasma spraying. Positive results have been also obtained while applying e-beam sputtering, ion-plasma deposition and magnetron sputtering. Nevertheless preferred plasma spraying application for thermal barrier coatings still continues due to its high productivity and versatility that permits to deposit metallic and ceramic materials of the ordered chemical and phase composition.Ytterbium and cerium oxides have been selected as oxides for stabilization of zirconium dioxide in order to obtain thermal barrier coatings. The paper also considers аn oxide system of zirconium dioxide: “hafnium oxide – yttrium oxide”, representing in itself the structure which is similar to zirconium dioxide.